From admission to discharge in mental health services: a qualitative analysis of service user involvement. (26th March 2015) - Wright, Nicola; Rowley, Emma; Chopra, Arun; Gregoriou, Kyriakos; Waring, Justin
Abstract: Background: User involvement and recovery are now widely used terms within the mental health policy, research and practice discourse. However, there is a question mark about the impact these ideas have in everyday practice. Of interest is the degree of involvement in key transitions of care. In particular, admission to and discharge from acute inpatient mental health wards. Objective: To explore the nature of service user involvement in the admission and discharge process into and out of acute inpatient mental health care. Design: A qualitative study using focus groups. Setting and Participants: One acute, inpatient mental health ward was the focus of the study. Seven uniprofessional focus group interviews were conducted with ward staff, community staff and service users (total number of participants = 52). Conventional, thematic qualitative techniques were used to analyse the data. Results: The data analysed and presented in this article relate to the loss of the service user voice at the key transition points into and out of acute inpatient care. Due to the lack of resources (inpatient beds and community care follow‐up), the role service users could play was diminished. In their narratives, clinical staff associated the person with the process and used language which dehumanized the individual. Conclusion: Service users experience numerous care transitions into and out of hospital. As there is the potential for these encounters to have a lasting negative effect, the importance of ensuring service users have a voice in what is happening to them is crucial.